THE TEACHERS’ MOTIVATING FACTORS IN TEACHING TOEFL AND IELTS TEST PREPARATION IN A PRIVATE INSTITUTION IN PEKANBARU, INDONESIA - Delvia Roza (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2023)
Many studies concentrate on the motivations of teachers in educational settings and with regard to teaching English as a foreign language. The motivations of teachers in a privatized environment like an English language centre would thus be interesting to research. The aim of the study was to investigate the teachers’ motivations in teaching TOEFL and IELTS test preparation by employing a qualitative approach with a case study. The purposive sampling method was used to recruit 10 teachers who had been instructing TOEFL and IELTS for more than ten years in one of the language training institutions in Pekanbaru. Four of the teachers had master's degrees in education and TESOL, while the others had bachelor's degrees with majors in English education. The data were gathered in person via audiotaped semi-structured interviews, and thematic analysis, as described by Braun & Clarke (2012), was used to examine the data. It was discovered that the factors that drove teachers to teach TOEFL and IELTS were: 1) their passion for teaching; 2) their test score improvement; 3) their self-development; 4) their satisfaction in helping students; 5) no required lesson plans; and 6) salary and career building.